2014
DOI: 10.3892/ol.2014.2230
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastic carcinoma: An analysis of 12 cases with a review of the literature

Abstract: The diagnosis of ameloblastic carcinoma is often difficult and the optimal treatment methods remain controversial. The current study retrospectively investigated the optimal diagnosis and treatment methods of 12 ameloblastic carcinoma patients at the West China Hospital of Stomatology, Sichuan University (Chengdu, China), and 20 patients selected from the PubMed database, were reviewed. The clinical features, diagnosis and outcome of the different treatments were evaluated. Ameloblastic carcinoma occurred in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
44
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 21 publications
15
44
4
3
Order By: Relevance
“…In the present study, we assessed 17 newly reported cases of maxillary AC from 2009 to 2017 (see Table 1). [2,6,[8][9][10][11][12][13] The age ranges from 21 to 77 years (mean age: 57.1 years) and the male to female ratio was 7.5:1, which was consistent with the Kruse et al report. [3] Most of the lesions (88.2%) similar to the present case and to previously reported cases occurred in the posterior portion of the maxilla.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, we assessed 17 newly reported cases of maxillary AC from 2009 to 2017 (see Table 1). [2,6,[8][9][10][11][12][13] The age ranges from 21 to 77 years (mean age: 57.1 years) and the male to female ratio was 7.5:1, which was consistent with the Kruse et al report. [3] Most of the lesions (88.2%) similar to the present case and to previously reported cases occurred in the posterior portion of the maxilla.…”
Section: Discussionsupporting
confidence: 80%
“…[3] Most of the lesions (88.2%) similar to the present case and to previously reported cases occurred in the posterior portion of the maxilla. [7,8,11] Clinically, swelling was the first clinical symptom in 94.1% of cases. Bleeding, pain, trismus and ulceration were associated with swelling in 47.05% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of radiation therapy in the treatment of ameloblastic carcinoma is controversial, with some reports favoring it 19 and others doubting its efficacy. 20 One study, in particular, used radiation therapy as adjuvant treatment for spindle cell variant of ameloblastic carcinoma and reported good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…While neglected and recurrent ameloblastoma can cause significant morbidity, mortality is extremely rare and is seen typically in a setting of maxillary ameloblastoma extending into the cranium [2,14,15]. The rare metastasizing ameloblastoma and ameloblastic carcinoma, each described in up to 2 % of patients with ameloblastoma, can also infrequently lead to mortality [2,4,5,8,21].…”
Section: Discussionmentioning
confidence: 99%